2001
DOI: 10.1515/jpm.2001.050
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant lavage and replacement in meconium aspiration syndrome with pulmonary hemorrhage

Abstract: We reported two case studies of meconium aspiration syndrome (MAS) with pulmonary hemorrhage in which we applied surfactant lavage and replacement. Surfactant lavage and replacement of MAS with pulmonary hemorrhage appears to be effective and safe adjunctive therapy. The relatively small replacement doses of surfactant required may be attributed to surfactant lavage followed by surfactant replacement. We suggest that surfactant lavage and replacement of MAS with pulmonary hemorrhage should be further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
2
12
0
2
Order By: Relevance
“…In human infants, the available data on lavage therapy in MAS are limited to several case series (20)(21)(22)(23)(24)(25) and two small randomized controlled trials (26,27). These studies have used both saline (20,21,24) and dilute surfactant (22)(23)(24)(25)(26)(27) as lavage fluids, with total lavage volumes of 3 to 48 ml/kg, and aliquot volumes ranging from 2 to 15 ml/kg.…”
mentioning
confidence: 99%
“…In human infants, the available data on lavage therapy in MAS are limited to several case series (20)(21)(22)(23)(24)(25) and two small randomized controlled trials (26,27). These studies have used both saline (20,21,24) and dilute surfactant (22)(23)(24)(25)(26)(27) as lavage fluids, with total lavage volumes of 3 to 48 ml/kg, and aliquot volumes ranging from 2 to 15 ml/kg.…”
mentioning
confidence: 99%
“…1 Different approaches have been proposed for the management of PH in newborn infants, including high airway pressures during mechanical ventilation, high frequency oscillation, 15 ECMO, 16 administration of recombinant activated Factor VII 17 and surfactant replacement therapy. 18 Although therapeutic lung lavage has been successfully used in MAS, with or without PH, 5,6,19 resulting in meconium removal from the alveoli and surfactant replacement such an approach has not been described for severe PH that can block central and peripheral airways similar to the situation in MAS. In our case we followed a small volume aliquot protocol, as our patient's extremely critical condition did not allow for the administration of larger lavage volumes as proposed for MAS.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study comparing ETT to LMA surfactant delivery, it was reported that surfactant delivery could be accomplished sooner in the LMA group with equivalent efficacy. 85 7 In animal studies, distribution of intratracheally instilled surfactant has been largely determined by gravity, and unaffected by the position of the chest. 89 Therefore, leaving the chest in a horizontal position may result in the most even distribution of surfactant to the lungs.…”
Section: Laryngeal Mask Airway (Lma) Administrationmentioning
confidence: 99%
“…Surfactant deficiency is associated with onset of respiratory distress syndrome (RDS), a major cause of morbidity and mortality in premature infants. 2 Surfactant is also effective in treating infants with meconium aspiration syndrome (MAS), pulmonary hemorrhage, 7 and pneumonia, although the evidence base for their use in these disease processes is much weaker than the primary indication of RDS. 8,9 Surfactant reduces surface tension, improves lung compliance, and stabilizes lung volumes at a lower transpulmonary pressure.…”
mentioning
confidence: 99%